EKSISTENSI BAHASA INDONESIA SEBAGAI BAHASA PENGANTAR PADA PROSES PEMBELAJARAN SISWA KELAS III DI SDN 4 CIBATU - Ramdhini, Restu; Nadiroti Muslihah, Neni; Nuriyanti, Risma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian serves as both the national language and the official medium of instruction in education. However, the dominant use of local languages in students’ daily lives may influence the use of Indonesian during learning activities. This study aims to describe the existence of Indonesian as the medium of instruction in the learning process of third-grade students at SDN 4 Cibatu, identify factors affecting its use, and examine teachers' efforts to maintain the use of Indonesian in school. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The research subjects consisted of the third-grade homeroom teacher and 42 students, including 20 male students and 22 female students. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that Indonesian remains the primary language of instruction in classroom learning. Approximately 70% of students were able to understand and use Indonesian effectively, while 30% still tended to use Sundanese in daily communication. Factors influencing the use of Indonesian include family environment, community environment, teachers, and students' language abilities. Teachers maintain the existence of Indonesian through language habituation, role modeling, literacy activities, and motivation. Thus, Indonesian maintains a strong position as the medium of instruction in the learning process at SDN 4 Cibatu.